Evaluation of the treatment with D-chiroinositol on levels of oxidative stress in pcos patients - В. Де Лео; А. Ла Марка; В. Каппеллі (Publishing House TRILIST, 2019)
Recent studies on the pathophysiology of infertility have shown that oxidative stress (OS) can be one of the causal factors. The OS is, by definition, an imbalance between the production of reactive oxygen species and antioxidant defense systems. It seems that oxidative stress plays an important role in almost all phases of human reproduction. In fact, reactive oxygen species are involved in the modulation of a large spectrum of reproductive functions such as oocyte maturation, ovarian steroidogenesis, corpus luteum functions and are involved in the processes of fertilization, embryo development and pregnancy, but also in some diseases that cause infertility. Polycystic ovary syndrome (PCOS) has recently been associated with increased oxidative stress, often put in relation to the syndrome's typical metabolic disorder. Inositol is an intracellular mediator of insulin, currently much used as a therapeutic agent in PCOS. While its main action takes place via insulin sensitization, little is known about the possible effects of other disorders, such as oxidative stress, associated with PCOS. Purpose of study was therefore to assess the effect of D-chiro-inositol on the state of oxidative stress in the follicular fluid of women with PCOS. Materials and methods. Follicular fluids were obtained from women who have turned to the Center for Diagnosis and Treatment of Sterility of Obstetrics and Gynecology of the University Hospital of Siena and Modena diagnosed with PCOS. The women were treated with D-chiro-inositol (500 mg x 2 per day) for 3 months before being subjected to cycles of in vitro fertilization. The state of oxidative stress was measured by marking of free thiol groups of proteins in the follicular fluid with 3-(N-maleimidopropionyl)-biocytin. Results. In our study we obtained a lesser presence of free thiol protein groups equal to 77.8% in the follicular fluid of women with PCOS not treated with D-chiro-inositol, compared to patients who instead have carried out such treatment. Conclusions. These results suggest that in PCOS women there is an increase of the oxidation of thiol groups of proteins follicular, correlated to a progressive increase of the oxidative stress and that the administration of D-chiro-inositol in patients with this disease seems to reduce the oxidation of thiol groups